Problems of the Past and Figures of Aging in Late and Early Wallace Stevens - D. Hagen, Benjamin (Age, Culture, Humanities: An Interdisciplinary Journal, 2020)
This paper reads a series of Wallace Stevens’s late poems (“Vacancy in the Park,” “The Irish Cliffs of Moher,” and “The Rock”) as well as his early poem “Sunday Morning” as figures of aging. These figures capture reflections on the past andpoetic efforts to make it feel real precisely at a moment when the past poses existential and temporal problems, at a moment when life’s circle seems to be closing. These late and early poems show that Stevens engages problems of the past and crafts figures of aging across his career, not just in a late or last phase. While the paper deploys the term “lateness” to describe Stevens’s poetic ethos and style, in this case, the term does not invoke the myth of the artist who has attained “old-age style” but a varied sense of ending, a kind of modernist ambience and activity of thinking and feeling the imminence and immanence of a life’s closing circle. Stevens’s figures of aging, moreover, emit and inventorysigns of detachment, emptiness, effervescence, dissipation, illusoriness, absurdity, and indifference but also affirmations of freedom, desire, and reverence. This affective inventory presents a “Wallace Stevens” who prompts us to ask (though he never provides an answer), “How might I age, grow older, draw near to my end otherwise?”